ANALISIS KOMPARASI PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PADA USAHATANI BAWANG MERAH VARIETAS BIRU LANCOR DAN BATU IJO DI KABUPATEN PROBOLINGGO - Utami, Ratih Apri; Firdaus, Ratna Nur; Aji, Joni Murti Mulyo; Agustina, Titin (Jurnal AGRISEP, 2024)
Consumer demand for shallots continues to increase yearly, influencing farmers to cultivate the commodity. One of the influential factors is the use of good-quality seeds. The superior seed varieties used in shallot cultivation in Probolinggo Regency, East Java Province are Biru Lancor and Batu Ijo. Both varieties are equally superior in production, but there are advantages and disadvantages to each of them. This study investigates the income disparities and influential factors between two varieties of shallot farming: Biru Lancor and Batu Ijo. The research in Dringu District, Probolinggo Regency, was conducted in four selected villages as sample areas. Employing multistage purposive sampling, 60 shallot farmers participated, with 30 utilizing Biru Lancor and 30 adopting Batu Ijo varieties. Data collection involved primary and secondary sources, with surveys and interviews. This research used quantitative methods, including income analysis, t-tests, and dummy multiple linear regression analysis using SPSS. The findings reveal significant differences in farming income between Biru Lancor and Batu Ijo varieties. Key factors influencing shallot farming income encompass seed type, land costs, pesticide expenses, labor expenditures, production yields, and selling prices. This research provides valuable insights into optimizing shallot farming practices and enhancing farmers' income levels.